Process Optimization Based on Biological Effects and Biomarker Contents of Camellia japonica L. for the Development of Anti-Hyperuricemic and Anti-Wrinkle Source - Seung-Yub Song; Dae-Hun Park; Ki-Wan An; Seung-Sik Cho (Separations, 2022)
The purpose of this study was to simultaneously develop anti-hyperuricemic and anti-wrinkle source using Camellia japonica leaf (CJ). CJ extract was prepared. Its contents of biomarkers and biological activities were then analyzed. First, we investigated the extraction efficiency. The extraction rate was 10% or less with hot water or 80% ethanol. HPLC analysis revealed that CJ extract contained rutin, hyperoside, isoquercitrin, chlorogenic acid (CGA), gallocatechin gallate (GCG), and phillygenin. As a result of measuring contents of biomarkers in the extract, CGA was detected in 20, 40, and 60% ethanol extracts. GCG showed the highest content in the hot water extract. Hyperoside and isoquercitrin showed the highest contents in the 80% ethanol extract. Philligenin showed an even content of 0.1% or more in all samples except for 40% ethanol extract. Rutin showed the highest content in 80% ethanol extract. Elastase inhibitory abilities of six extracts and PPRM were investigated at a concentration of 0.5 mg/mL. Results revealed that PPRM and 80% ethanol extract showed about 80% and 62% inhibition, respectively. As a result of comparing elastase inhibitory activities of biomarkers, hyperoside, isoquercitrin, and philligenin showed higher activities. Among six extracts, the extract that could be used as an anti-hyperuricemic source was 80% ethanol extract. When xanthine oxidase (XO) inhibitory activities of biomarkers were evaluated, rutin and hyperoside showed excellent activities. In particular, when XO activity was measured by mixing rutin and hyperoside with 80% ethanol extract, the same efficacy as 80% ethanol extract was obtained. It was predicted that 80% ethanol extract could be used simultaneously as an anti-hyperuricemic and anti-wrinkle source. Further studies are needed to determine anti-hyperuricemic activities of rutin and hyeproside in vivo.